Penerapan Metode Yield/Revenue dengan RevPar: Studi Pada Hotel and Convention X - Anita Swantari; Haryo Wicaksono; Filma Festivalia; Heny Ratnaningtyas (At-Tadbir : jurnal ilmiah manajemen, 2021)
This study aims to determine the application of yield/revenue with RevPAR (Revenue Per Available Room). This type of research is quantitative research. The data analysis method in this study uses the trend analysis method. Data sources were obtained from Hotel X & Conventions in the form of daily hotel reports, revenue management forecast reports and pattern reports from January to December 2018. The results show that Yield/Revenue Management has been implemented well at Hotel X & Conventions Kelapa Gading in 2018 by making a RevPAR estimate that is close to the actual, with the difference between the estimated data and the actual data being only 5.34% to 17%. The highest RevPAR was in August 2018 which was Rp. 585,690,- and the lowest was in February 2018 which was Rp. 474,114. The conclusion of this study is that Hotel X & Conventions Kelapa Gading has implemented yield/revenue management well in 2018 by carrying out RevPAR estimates which are almost in accordance with the actual, with the difference between the estimated data and the actual data.Keywords: Yield/Revenue Management, RevPar(Revenue Per Available Room)